PELATIHAN DAN PENGEMBANGAN KOMPETENSI BAHASA INGGRIS BAGI GURU-GURU DAN STAFF SEKOLAH DASAR SDN 104211 - Masriani Mery Rosmida Silalahi; Rani Rakasiwi; Winmery Habeahan; Lasrida Sigalingging; Marlina Tampubolon; Rachel Siahaan (Jurnal Pengabdian Pada Masyarakat METHABDI, 2021)
This community service aims to improve English language skills for teachers and elementary school staff at SDN 104211. The method applied is the provision of materials and practice. This service uses a descriptive method with a qualitative approach. Which aims to describe learning the introduction of English. Collecting data using observation techniques, interviews, documentation with data collection tools, namely interview guides, observation guidelines, field notes, and documents. The research subjects were teachers and elementary school staff at SDN 104211. The results showed: (1) in planning language recognition learning there were themes, indicators, main activities, media adapted to students' needs (2) in implementation, teachers carried out language recognition learning English is in accordance with the lesson plans, (3) the supporting factors for learning English introduction are the availability of learning media for the introduction of English provided by institutions and teachers. (4) the inhibiting factor in learning the introduction of English is not the main language for children so that teachers must be creative in teaching; classroom teachers do not have sufficient knowledge of English; Child development is a consideration so that children are not depressed.